Pemaknaan The Power of Emak-Emak di Media Sosial - Rahman Asri (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2019)
The movement of the Power of Emak-Emak in the 2019 Presidential Election became significant considering a large number of female voters in the 2019 Presidential Election. Besides potential voters, women were also active social media users. This study aims to see the meaning of mothers towards the movement of The Power of Emak-Emak in relation to women's political participation in Indonesia. This study uses the Reception Analysis by Stuart Hall. The approach used is qualitative by conducting in-depth interviews with four active social media users. The results of the study showed that the dominant meaning of The Power of Emak-Emak Movement was part of the active role in women's political participation in the 2019 Presidential Election.